Gibberellin control of stamen development: a fertile field - Plackett, Andrew R.G; Thomas, Stephen G; Wilson, Zoe A; Hedden, Peter (Trends in plant science, 2011)
Stamen development is governed by a conserved genetic pathway, within which the role of hormones has been the subject of considerable recent research. Our understanding of the involvement of gibberellin (GA) signalling in this developmental process is further advanced than for the other phytohormones, and here we review recent experimental results in rice (Oryza sativa) and Arabidopsis (Arabidopsis thaliana) that have provided insight into the timing and mechanisms of GA regulation of stamen development, identifying the tapetum and developing pollen as major targets. GA signalling governs both tapetum secretory functions and entry into programmed cell death via the GAMYB class of transcription factor, the targets of which integrate with the established genetic framework for the regulation of tapetum function at multiple hierarchical levels.